Antropologia trychotomiczna Orygenesa - Turzyński, Piotr (Vox Patrum, 2015)
Origen was one of the greatest biblical scholars of the early Church, having written commentaries on most of the books of the Bible. He recognized great authority of the scripture. In anthropology he gave attention to the text of saint Paul: “May the God who gives us peace make you holy in every way and keep your whole being – spirit, soul, and body – free from every fault at the coming of our Lord Jesus Christ” (1Thess 5:23). According to this text Origen recognized in human being three elements. He tried to unite trichotomy with a concept of division of human being into two parts: interior and exterior man. Spirit in this concept is soul’s teacher and a special form of participation in the divine being. In a sense spirit is ontological image of God in man and for man it is impossible to lose it. Soul is the center of man in which he makes decisions. Soul was originally created in close proximity to God, with the intention that it should explore the divine mysteries in a state of endless contemplation. The body unites man with the whole created world and gives him material aspect. Origen’s anthropology is very complicated but more dynamic then static division on body and soul. If the soul is going to spirit, it become more spiritual, otherwise if the soul is close to the body, it become more materialistic. In this view without any doubt the human soul is posed between spirit and body and is able to acquiesce the desires of spirit but is able to let itself to be led by carnal desires, too. According to Origen man is body, because is creature, which dies, but through the body is able to communicate with material world. Man is soul because lives and is able to choose. Man is spirit because is open to God and is able to recognize and love God. Trichotomic anthropology shows that ontological and moral aspects of human being permeate each other and it demonstrates the interior drama and struggle, which always exists in man.